2005
DOI: 10.1128/aac.49.8.3501-3512.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Spectrum of PPI-0903M (T-91825), a Novel Cephalosporin, Tested against a Worldwide Collection of Clinical Strains

Abstract: PPI-0903M is a novel N-phosphono-type cephalosporin active against oxacillin-resistant staphylococci and many other gram-positive organisms. This study evaluated the in vitro activity and spectrum of PPI-0903M against 1,478 recent clinical isolates collected from 80 medical centers (22 countries). PPI-0903M demonstrated broader in vitro activity against gram-positive bacteria, particularly against multidrug-resistant staphylococci and streptococci of current clinical concern, than currently available extended-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 15 publications
14
136
0
4
Order By: Relevance
“…14,15 We have confirmed the antimicrobial activities of CPT and ME with strains from our own collection (Supporting Information), including S. aureus isolates ATCC 29213 (Clinical and Laboratory Standards Institute (CLSI) susceptible standard), vancomycin-resistant MRSA clinical isolates VRS1 and VRS2, and linezolid-resistant MRSA isolates NRS119 and NRS120. Linezolid and vancomycin are commonly used in treatment of MRSA infections, although documented resistance to these agents is worrisome.…”
mentioning
confidence: 80%
“…14,15 We have confirmed the antimicrobial activities of CPT and ME with strains from our own collection (Supporting Information), including S. aureus isolates ATCC 29213 (Clinical and Laboratory Standards Institute (CLSI) susceptible standard), vancomycin-resistant MRSA clinical isolates VRS1 and VRS2, and linezolid-resistant MRSA isolates NRS119 and NRS120. Linezolid and vancomycin are commonly used in treatment of MRSA infections, although documented resistance to these agents is worrisome.…”
mentioning
confidence: 80%
“…The MIC 90 for 100 strains of hVISA and VISA (19 VISA and 81 hVISA strains) was also 2 g per ml (range, 0.25 to 4 g per ml) (290). A few animal studies have shown ceftaroline to be useful for the treatment of MRSA infections, and in mice, ceftaroline was comparable or superior to vancomycin, linezolid, teicoplanin, and arbekacin (136).…”
Section: Potentially Active Antimicrobials In Developmentmentioning
confidence: 97%
“…Particularly, the prevalence of MRSA (methicillin-resistant Staphylococcus aureus) in hospitals has stimulated the development of more potent carbapenems (ME 1036 [64]) and cephalosporins (PPI 0903M [65]), characterized by very bulky substituents on the bicyclic skeletons. The lethal action of such antibiotics is due to their high affinity for PBP 2a .…”
Section: Discussionmentioning
confidence: 99%
“…Instead of increasing the angular strain and the N1 pyramidality (''twisted amide'') in the azetidinone ring of 1,4-fused bi- [64,65] or tricyclic systems [66], we considered flexible 1,3-bridged bicyclic systems featuring a ''planar amide'' and a large ring susceptible to generate a lot of conformers. Such azetidinones, endowed with a thienamycin-like side-chain at C3 and the related stereochemistry at C3-C5, are readily accessible via a convergent RCM strategy, as illustrated by the synthesis of the 13-membered bicycles E-11 and 12 from the commercial chiron 7, precursor of 10.…”
Section: Discussionmentioning
confidence: 99%